Identifying miRNAs associated with amyotrophic lateral sclerosis and mitochondrial dysfunction through bioinformatics approaches - Baykal, Gulcin; Erkal, Burcin; Korkut, Senay Vural (KARE PUBL, 2023)
study, we identify genes in ALS. miRNAs involvement silico predictions miRNA biomarkers, silico tools sequence detailed functional Consequently, false and the accuracy
Keywords: Amyotrophic lateral sclerosis; biomarkers; miRNAs; mitochondrial dysfunction; SPINAL-CORD; VCP MUTATIONS; BCL-2; EXPRESSION; PROTEINS; COMPLEX; SOD1; DEGENERATION; AUTOPHAGY; MIR-125B; Biochemistry & Molecular Biology